Weighting and sequence of use of different lab environment in the teaching-learning process - Alves, Gustavo R. (2017)
The teaching-learning process has been a constant target of studies, particularly in Higher Education, in consequence of the annual increase of new students that, in merely statistic terms, have been progressively decreasing the application averages. The concern with the maintenance of a certain quality level in the training of these students, conjugated with the will to widen the access to all of those who finish Secondary School Education, has triggered a greater intervention from the education specialists, in partnership with the teachers of all Higher Education areas, in the problem analysis. Considering the particular case of Sciences and Engineering, where the laboratorial component in the teaching-learning process takes a relevant role, recent breakthrough of the educational technologies has created valid alternatives for the traditional laboratorial environments, namely the virtual and remote laboratorial environments, not totally explored yet. In parallel, it is also witnessed a rising concern with the analysis of learning styles, as the outcome of the rising heterogeneity that characterizes, in a global way, the students who choose those Higher Education areas. Having - the teachers - available a rising variety of educational resources and teaching methods before a wide number of students with unique learning styles, it is important to study in what way it is possible to ponder and sequence the different types of laboratorial environments, to achieve the general purpose of increasing the knowledge level and the students‘ experimental competences who chose the Sciences and Engineering.